الأساس القانوني لدعوى المنافسة غير المشروعة وشروطها (Numerus academy review, 2026)
An unfair competition action is not an ordinary civil action based on the rules oftort in the Obligations Act, but an action of a special nature in view of the special natureof the right it protects.